The Axin/TNKS complex interacts with KIF3A and is required for insulin-stimulated GLUT4 translocation - Guo, Hui-Ling; Zhang, Cixiong; Liu, Qi; Li, Qinxi; Lian, Guili; Wu, Di; Li, Xuebin; Zhang, Wei; Shen, Yuemao; Ye, Zhiyun; Lin, Shu-Yong; Lin, Sheng-Cai (Cell research, 2012)
Insulin-stimulated glucose uptake by the glucose transporter GLUT4 plays a central role in whole-body glucose homeostasis, dysregulation of which leads to type 2 diabetes. However, the molecular components and mechanisms regulating insulin-stimulated glucose uptake remain largely unclear. Here, we demonstrate that Axin interacts with the ADP-ribosylase tankyrase 2 （TNKS2） and the kinesin motor protein KIF3A, forming a ternary complex crucial for GLUT4 transiocation in response to insulin. Specific knockdown of the individual components of the complex attenuated insulin-stimulated GLUT4 translocation to the plasma membrane. Importantly, TNKS2-/- mice exhibit reduced insulin sensitivity and higher blood glucose levels when re-fed after fasting. Mechanistically, we demonstrate that in the absence of insulin, Axin, TNKS and KIF3A are co-localized with GLUT4 on the trans-Goigi network. Insulin treatment suppresses the ADP-ribosylase activity of TNKS, leading to a reduction in ADP ribosylation and ubiquitination of both Axin and TNKS, and a concurrent stabilization of the complex. Inhibition of Akt, the major effector kinase of insulin signaling, abrogates the insulin-mediated complex stabilization. We have thus elucidated a new protein complex that is directly associated with the motor protein kinesin in insulin-stimulated GLUT4 translo- cation.